Mapping and Diagnosing the Development of Philosophy of Education in Primary Education: A Bibliometric Analysis - Yuli Setiawati; Brigida Intan Printina; Wina Anggraini; Sintia; Salsa Cahya Septiani; Umy Khafifah; Tenia Diva Putriana (International Journal of Education, Language, and Social Science, 2026)
This study analyzes the development of philosophy of education research at the primary education level through a bibliometric approach. Data were obtained from the Scopus database using systematic search criteria, resulting in 573 articles published between 2016 and 2025. The analysis was conducted using R software through the bibliometrix package and the Biblioshiny interface to identify trends in scientific production, conceptual structure, and thematic evolution. The results indicate a significant increase in the number of publications, with an annual growth rate of 31.3%, reflecting growing academic interest in this field. However, the findings also reveal disparities in scientific production across countries, low levels of international collaboration, and fragmentation in the conceptual structure. Conceptual analysis highlights the dominance of core themes such as epistemology, ethics, and phenomenology, as well as the emergence of contemporary themes such as critical thinking and sustainability. Thematic evolution indicates a shift from classical philosophical approaches toward more contextual and applied orientations in education. This study contributes by providing an integrated mapping and diagnosis of the field’s development and emphasizes the importance of strengthening conceptual coherence, global collaboration, and more systematic research directions to support the advancement of philosophy of education in primary education.